Borderline Metal Centers on Nonporous Metal‐Organic Framework Nanowire Boost Fast Li‐Ion Interfacial Transport of Composite Polymer Electrolyte. Issue 40 (1st September 2022) - Xu, Jianqi; Ma, Guixin; Wang, Ning; Zhao, Simin; Zhou, Jisheng
Abstract: Metal‐organic frameworks (MOFs) fillers are emerging for composite polymer electrolytes (CPEs). Enhancing Lewis acid–base interaction (LABI) among MOFs, polymer and Li‐salt is expected to promote Li + ‐transport. However, it is unclear how to customize a strong LABI interface. The large surface‐area of classical MOFs also interferes with clarifying the LABI influence on Li + ‐transport. Herein, Bi 3+ as metal centers to design colloidal‐dispersed nonporous MOFs (Bi/HMT‐MOFs) nanowire with a surface‐area of only 17.13 m 2 g −1 to prepare polyethylene oxide (PEO)‐based CPEs (BMCPE) is chosen. The nonporous feature can exclude the surface‐area effect on Li + ‐transport. More interestingly, Bi 3+ is a typical borderline acid, which can interact with both hard‐basic PEO and soft‐basic Li‐salt anion. Accordingly, Bi/HMT‐MOFs are uniformly dispersed in the BMCPE to form a strong LABI interface with PEO and Li‐salt, promoting Li‐salt dissociation and providing rapid Li + ‐transport channels. Despite the ultralow surface‐area of Bi/HMT‐MOFs, BMCPE exhibits significantly enhanced ion‐conductivity and Li + transference number, which completely rival traditional MOFs‐filled CPEs. BMCPE also enables symmetric and full cells with excellent high‐rate performance and long‐term cycling stability. In contrast, when Bi 3+ sites are obscured, electrochemical performances are obviously decreased. Therefore, employing borderline metal centers will be an effective strategy to construct a LABI interface for high‐performance MOFs‐filled CPEs. Abstract : Colloidal‐dispersed Bi/HMT‐MOFs nanowires are designed as multifunctional fillers to prepare a PEO‐based composite solid electrolyte with a strong Lewis acid–base interaction interface. A strong interface can effectively promote the mobility of PEO chain and dissociation of Li‐salt to achieve rapid Li + transport, so the electrolyte films in both symmetrical and full cells exhibit excellent performances.